2022
DOI: 10.3390/ijerph191610179
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Group Identification on Death Anxiety: The Chain Mediation Role of Close Relationships and Self-Esteem

Abstract: Based on the terror management theory (TMT), this study integrated self-esteem and close relationships to explore the effects of group identification on death anxiety. Five hundred and four participants completed the Death Anxiety, Rosenberg Self-Esteem, Social Identity, and Inclusion of Other in the Self scales via online platforms. There were significant correlations among group identification, close relationship, self-esteem, and death anxiety. Group identification had a significant negative predictive effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Thus, changes in death anxiety in young people may be related to the breakdown of family-centered intimacy and the re-establishment of individual-centered intimacy. Having a self-centered social network (intimacy) can help individuals regulate their emotions and gain a sense of meaning and value in life, thereby reducing anxiety and fear of death 42 . In addition, we also found that the unemployed (and possibly college students) showed remarkable levels of death anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, changes in death anxiety in young people may be related to the breakdown of family-centered intimacy and the re-establishment of individual-centered intimacy. Having a self-centered social network (intimacy) can help individuals regulate their emotions and gain a sense of meaning and value in life, thereby reducing anxiety and fear of death 42 . In addition, we also found that the unemployed (and possibly college students) showed remarkable levels of death anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, mortality salience can motivate individuals to establish and maintain intimacy, while the breakdown of intimacy can increase death thinking (Mikulincer et al, 2003). Research has shown that group identity can alleviate death anxiety through intimate relationships (Xiao et al, 2022). Mortality salience can also enhance the defense mechanisms of healthcare providers by increasing their relationship satisfaction (Chen et al, 2021), and marriage can also buffer deathrelated thoughts (Yaakobi, 2018).…”
Section: The Moderating Role Of Connection Thinkingmentioning
confidence: 99%
“…In a two-year study by Prickett and Timmermans (2022) of a volunteer community in the United States that gathered to bury unclaimed or “abandoned” infants, it was found that people who gathered together transformed potentially negative factors into group-forming events and aligned social experiences, which is somewhat similar to the experience of intimate relationships ( Bailey and Walter, 2016 ; Ådland et al, 2022 ), which may create a sense of group solidarity and enhance emotional energy, thereby helping cancer patients to mitigate the threat of death. Currently, a large body of research demonstrates that intimate relationships, in addition to having a positive impact on human survivorship and reproductive adaptability ( Grebe et al, 2019 ), play an important role in dealing with death-related anxiety and fear ( Xiao et al, 2022 ). Plusnin et al (2018) found that several fundamental characteristics of intimate relationships contribute to their defensive roles against fear and anxiety about death.…”
Section: Introductionmentioning
confidence: 99%